REWARD AND SUPERVISOR SUPPORT AS KEY DRIVERS OF EMPLOYEE RETENTION IN MALAYSIA - Hussain, Yusmawati; Zakaria , Mohd Nazri; Salleh , Muhammad Zulfaris Mohd; Hassan , Hasannuddiin (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Employee retention remains a pressing challenge for Malaysian organizations, driven by heightened job mobility and shifting workforce expectations. This paper examines the roles of reward and supervisor support as complementary drivers of retention, drawing on Social Exchange Theory to frame their combined influence. Rewards are positioned as sources of extrinsic satisfaction through fair compensation and recognition, while supervisor support provides socio-emotional resources that build trust, care, and organizational attachment. Together, these factors reinforce employees’ commitment and reduce turnover intentions, offering a more sustainable pathway to retention than when applied in isolation. By synthesizing recent empirical findings with theoretical perspectives, this study contributes to the academic literature on employee retention in emerging economies while offering practical guidance for managers and HR practitioners seeking to develop integrated retention strategies in Malaysia’s competitive labour market.